Code-switching and language control. Issue 5 (11th February 2016) - GREEN, DAVID W.; WEI, LI
Abstract : Bilingual speakers can use one of their languages in a given interactional context or switch between them when addressing different speakers during the same conversation. Depending on community usage bilingual speakers may insert single lexical forms from one language into the morphosyntactic frame of another or alternate between languages at clause boundaries. They may also engage in dense code switching with rapid changes of language within a clause during a conversational turn (Green & Li, 2014 ). These varieties of language use configure the same speech production mechanism and so a theory of code-switching must be part of a theory that accounts for the range of bilingual speech. Does the proposal described in Goldrick, Putnam and Schwartz (2016 ) meet these criteria?